Enrichment of the Postdischarge GRACE Score With Deceleration Capacity Enhances the Prediction Accuracy of the Long-Term Prognosis After Acute Coronary Syndrome - Duan, Shoupeng; Wang, Jun; Yu, Fu; Song, Lingpeng; Liu, Chengzhe; Sun, Ji; Deng, Qiang; Wang, Yijun; Zhou, Zhen; Guo, Fuding; Zhou, Liping; Wang, Yueyi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac autonomic nervous system (ANS) imbalance has been well documented to provide a critical foundation for the development of acute coronary syndrome (ACS) but is not included in the postdischarge GRACE score. We investigated whether capturing cardiac ANS-related modulations by 24-hour deceleration capacity (DC) could improve the capability of postdischarge Global Registry of Acute Coronary Events (GRACE) score, to predict prognosis after ACS. Method: Patients with ACS were assessed with 24-hour Holter monitoring in our department from June 2017 through June 2019. The GRACE score was calculated for postdischarge 6-month mortality. The patients were followed longitudinally for the incidence of major adverse cardiac events (MACEs), the composite of death and nonfatal myocardial infarction. To assess the improvement in its discriminative and reclassification capabilities, the GRACE score with DC model was compared with a model using the GRACE score only, using area under the receiver-operator characteristic curve (AUC), Akaike’s information criteria, the likelihood ratio test, the category-free net reclassification index (NRI) and integrated discrimination improvement (IDI). Results: Overall, 323 patients were included. After the follow-up period (mean, 43.78 months), 41 patients were found to have developed MACEs. DC adjusted for the GRACE score independently predicted the occurrence of MACEs with an adjusted hazard ratio (HR) of 0.885 and 95% CI of 0.831-0.943 (p<0.001). Moreover, adding DC to the GRACE score only model increased the discriminatory ability for MACEs, as indicated by the likelihood ratio test (χ2=9.277, 1 df; p<0.001). The model including the GRACE score combined with DC yielded a lower corrected Akaike’s information criterion compared to that with only the GRACE score. Incorporation of the DC into the existing model that uses the GRACE score enriched only the net reclassification indices (NRIe>0 7.3%, NRIne>0 12.8%, NRI>0 0.200; p=0.003). Entering the DC into the GRACE score model enhanced discrimination (IDI of 1.04%, p <0.001). Conclusion: DC serves as an independent and effective predictor of long-term adverse outcomes after ACS, even after adjusting for the postdischarge GRACE score. Integration of DC and the postdischarge GRACE score significantly enhanced the discriminatory capability and precision in the prediction of poor long-term follow-up prognosis.